Tetra-μ-2-methylbenzoato-κ(8) O:O′-bis[(ethanol-κO)copper(II)] - Ni, Sheng-Liang (International Union of Crystallography, 2011)
In the title dinuclear complex, [Cu(2)(C(8)H(7)O(2))(4)(C(2)H(5)OH)(2)], four 2-methylbenzoato anions form a cage around two Cu(II) ions in a syn–anti configuration. Two ethanol molecules coordinate the Cu atoms in apical positions, giving an overall square-pyramidal coordination geometry. The Cu⋯Cu separation is 2.600 (1) Å. In the crystal, molecules are assembled into chains extending in [001] through O—H⋯O hydrogen bonds.